Employee Performance In The Perspective Of Job Demand- Resource: The Role Of Work Ethic As A Personal Resource And Workload As A Job Demand With Job Satisfaction As A Mediator - Nita Ayu Saputri; Suhardi Suhardi; Mohammad Makrus (JURNAL ECONOMINA, 2026)
This study aims to analyze employee performance from the perspective of Job Demands–Resources (JD-R) by examining the role of work ethic as a personal resource and workload as a job demand, as well as job satisfaction as a mediating variable in village employees in Pangkalpinang. This research is motivated by the increasing complexity of public service demands and the importance of understanding the psychological mechanisms that affect employee performance in the public sector. The research uses an explanatory quantitative approach with survey data collected from employees in several villages in Pangkalpinang. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables. The results of the study show that work ethic has a positive and significant effect on job satisfaction and employee performance. Job satisfaction has also been shown to have a significant effect on employee performance and is able to partially mediate the relationship between work ethic and employee performance. On the other hand, workload does not have a significant effect on job satisfaction or employee performance. These findings indicate that employees tend to be able to adapt to routine administrative pressures in the public sector environment. The results of the study show that the motivational mechanism sourced from personal resources is more dominant than the strain mechanism in explaining employee performance at the local government level. This research contributes to the development of JD-R theory by showing the strong role of personal resources compared to job demand in shaping employee outcomes in the public sector. Practically, the results of the study imply that local governments need to prioritize strengthening work ethic and employee psychological well-being in order to improve organizational performance and the quality of public services in a sustainable manner.